Pengaruh Hedonic Motive dan Shopping Lifestyle Terhadap Impulsive Buying Pada E-Commerce Shopee di Kota Mataram - I Gusti Ayu Anindita Hendryadewi; Handry Sudiartha Athar (Postgraduate, University of Mataram, 2025)
This research aims to determine the effect of hedonic motive and shopping lifestyle on impulsive buying on Shopee e-commerce in Mataram City. The sample of this study was Shopee e-commerce users in Mataram City who made impulsive purchases. The data analysis method used was multiple linear regression. The results showed that hedonic motive and shopping lifestyle significantly influenced impulsive buying on Shopee e-commerce in Mataram City. This study contributes to the understanding of consumer behavior in the context of e-commerce and can be used as a reference for business actors to develop effective marketing strategies.